Spatial Structure and Decadal Spatiotemporal Distribution of the Anchoveta ( Engraulis ringens ) in the Marine Ecosystem of the Peruvian Current Between 1985 and 2024 - Pedro Ramiro Castillo; Han Xu; Gustavo Cuadros; Daniel Grados; Carlos Valdez; Rodolfo Cornejo; Marissela Pozada‐Herrera (Fisheries Oceanography, 2025)
This paper presents the spatial structure with geostatistical analysis and decadal spatiotemporal distribution of anchoveta according to the Pacific Decadal Oscillation index, its implications for the anomalous events of the oceanographic conditions of the Northern Region of the Humboldt Current System (NRHCS), and areas of high anchoveta abundance found in the analyzed period. The acoustic data came from the Hydroacoustic Pelagic Resources Assessment Surveys carried on by the Instituto del Mar del Peru (IMARPE), and the oceanographic data came from satellite images of sea surface thermal anomalies (SSTA) between 1985 and 2024. The results showed that anchoveta has had a positive linear trend, with a high positive spatial autocorrelation and a structure spatially dependent on invironmental conditions in space and time. In the cold decadal periods, anchoveta were found a little far from the coast, distributed in high concentrations mainly in the north‐central region, while in the warm decadal periods, they were found close to the coast and with greater abundance towards the central zone; exceptional was in the warm period of 1985–1988, where anchoveta distribution was wide and generally dispersed. The trend in the warm decadal periods was negative, and in the decadal periods, it was positively influenced by El Niño events: 1997–1998 and 2015–2016, with a decrease in biomass recorded in 1998 and 2015. In the last cold period, 2017–2024, it was influenced by the warm year of 2023. Between 2000 and 2024, anchoveta biomass averaged 8.26 million tons, with an average biomass of 7.46 million tons for the north‐central region between 2004 and 2024.